Архівна освіта в Україні: традиції й тенденції - Бездрабко, В.В. (Український історичний журнал, 2017)
Розглянуто традиції та новітні тенденції розвитку архівної освіти в нашій
країні. Визначено й охарактеризовано дві моделі освіти: історико-архівну та
соціокомунікаційну. Зауважено на особливостях зарубіжного досвіду підготовки
фахівців для архівної галузі й можливостях його запозичення. Акцентовано увагу на сучасному нормативно-правовому реґулюванні розвитку архівної освіти в Україні. We have considered the tradition and newest tendencies of development of archival education
in Ukraine. It was determined and characterized two models of archival education:
historical archival and socio-communicative. The point was made on the features
of the foreign experience of training for archival industry and capabilities of its borrowing.
It was brought to a focus on the present legal regulation of archival education in Ukraine.